The Impact of Tourism on Social Change - Dewi Puspasari. T; T. Safir Iskandar Wijaya; Muhammad Sahlan (Winaya Inspirasi Nusantara Foundation, 2021)
The development of tourism in Simeulue resulted in social changes in the Nencala Village community in Simeulue, shaping the mindset and habits and lifestyle of the community changed in a relatively short time towards a modern and consumptive life, social change also had an impact on village development, thus making the village more advanced, especially in tourism development which became more well maintained and preserved. The purpose of the research is to find out, describe and analyze the social changes that occur in community members and infrastructure in Nencala Village, West Teupah District. This research is descriptive qualitative research in the form of field research by taking the location of Nencala Village, West Teupah District, Simeulue Regency. The techniques used in using data are observation, interviews and documentation. From the results of the study concluded that the development of tourism was well received by the community in Nencala Village. The factors that influence social change are the acceptance of new elements, acculturation, migration, acceptance of changes in living habits from traditional to semi-modern, an attitude of respect for the work of others and the desire to progress. tourism development in Nencala Village, West Teupah District turned out to have many positive impacts rather than negative impacts on local communities both from the physical, socio-cultural and economic aspects. Thus, the development of tourism in Nencala Village, West Teupah District, Simeulue Regency can improve the standard of living of the community for the better.